Counseling for Special Needs Children Experiencing Bullying Through Rational Emotive Behavior Therapy (REBT) Approach - Hidayati, Nurul; Idhartono, Amelia Rizky (Proceeding of International Conference on Special Education in South East Asia Region, 2024)
When a family having a child with special needs, the happiness that parents experience is mixed with a variety of other emotions such as shock, self-guilt or partner, to worry about their child's future. ABK needs special attention and service. ABK requires special attention, help, service, and learning methods. Likewise, ABK parents need special support to make it easier for them to adapt, accept, and then educate their ABK optimally. One of the forms of support that is needed is counseling. Counseling for ABKs needs to be done among others so that they do not feel alone and have a support group to make them more resilient in the face of various problems and challenges in life. Especially when ABK suffered bullying, where ABK included those who were vulnerable to bullyed because of their different conditions. Rational Emotive Behavioral Therapy (REBT) provides an overview of how counseling for ABK victims of bullying through the REBT approach can help them in addressing the problems associated with the impact of ABK's Bullying.